2019
DOI: 10.1126/sciadv.aau4255
|View full text |Cite
|
Sign up to set email alerts
|

Type III interferon signaling restricts enterovirus 71 infection of goblet cells

Abstract: Recent worldwide outbreaks of enterovirus 71 (EV71) have caused major epidemics of hand, foot, and mouth disease with severe neurological complications, including acute flaccid paralysis. EV71 is transmitted by the enteral route, but little is known about the mechanisms it uses to cross the human gastrointestinal tract. Using primary human intestinal epithelial monolayers, we show that EV71 infects the epithelium from the apical surface, where it preferentially infects goblet cells. We found that EV71 infectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 40 publications
6
91
0
Order By: Relevance
“…Once internalized, it is possible that the interaction between FcRn and echoviruses is altered by the low pH of endosomes, which may facilitate subsequent genome release and/or endosomal escape. We have shown that E11 preferentially infects enterocytes (10), with enhanced infection from the basolateral surface of human intestinal epithelial (HIE) cells (29). This polarity of infection is consistent with the enhanced expression of FcRn in enterocytes in the intestine and its enrichment to the basolateral surface.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Once internalized, it is possible that the interaction between FcRn and echoviruses is altered by the low pH of endosomes, which may facilitate subsequent genome release and/or endosomal escape. We have shown that E11 preferentially infects enterocytes (10), with enhanced infection from the basolateral surface of human intestinal epithelial (HIE) cells (29). This polarity of infection is consistent with the enhanced expression of FcRn in enterocytes in the intestine and its enrichment to the basolateral surface.…”
Section: Discussionsupporting
confidence: 70%
“…This polarity of infection is consistent with the enhanced expression of FcRn in enterocytes in the intestine and its enrichment to the basolateral surface. Following replication, E11 is released bidirectionally from HIE from both the apical and basolateral domains (29). Given that FcRn mediates bidirectional transport (30), this raises the possibility that echoviruses could be transported from either the apical or basolateral domains to cross the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pharmacological inhibitors for the stimulation of viral infection has been described in many studies of immortalized cell lines (39,47,80) and more recently for viral infection of intestinal organoids (81). The mechanism of action of Rux is well defined, as it specifically targets the JAK kinases (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, only 2 of 12 WT animals and 2 of 13 hFcRn Tg32 animals had any detectable virus in liver and 0 of 12 WT mice and 1 of 13 hFcRn Tg32 mice had detectable virus in the brain, although in both cases, viral titers were very low ( Figure 1B, 1F). Because many enteroviruses are restricted by type I IFN signaling in small animal models and because we have previously shown that E11 is sensitive to recombinant IFN-b treatment 24 , we reasoned that type I IFNs might play a key role in restricting E11 infection in vivo. To test this, we infected suckling mice deficient in type I IFN signaling (IFNAR -/-) with 10 4 PFU E11 by the IP route.…”
Section: Human Fcrn and Type I Ifn Signaling Are Key Host Determinantmentioning
confidence: 99%